Factors That Influence the Adoption of Enterprise Architecture by Public Sector Organizations: An Empirical Study - Ahmad N.A.; Drus S.M.; Kasim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Least squares approximations; Enterprise Architecture; Environmental contexts; Malaysian public sectors; Organizational readiness; Partial least square (PLS); Public sector organization; Structural equation modeling; Technology-organization-environment frameworks; Decision making